Impaired regeneration: A role for the muscle microenvironment in cancer cachexia. (June 2016) - Talbert, Erin E.; Guttridge, Denis C.
Abstract: While changes in muscle protein synthesis and degradation have long been known to contribute to muscle wasting, a body of literature has arisen which suggests that regulation of the satellite cell and its ensuing regenerative program are impaired in atrophied muscle. Lessons learned from cancer cachexia suggest that this regulation is simply not a consequence, but a contributing factor to the wasting process. In addition to satellite cells, evidence from mouse models of cancer cachexia also suggests that non-satellite progenitor cells from the muscle microenvironment are also involved. This chapter in the series reviews the evidence of dysfunctional muscle repair in multiple wasting conditions. Potential mechanisms for this dysfunctional regeneration are discussed, particularly in the context of cancer cachexia.